Effects of light intensity and nutrients on the lipid content of marine microalga (diatom) Amphiprora sp. for promising biodiesel production - Jayakumar, Saravanan; Bhuyar, Prakash; Pugazhendhi, Arivalagan; Mohd Hasbi, Ab. Rahim; Gaanty Pragas, Maniam; Govindan, Natanamurugaraj (Elsevier B.V., 2021)
In this research investigation, three microalgal species were screened (Pleurosigma sp., Amphora sp., and Amphiprora sp.) for lipid content before choosing the potential microalgae for biodiesel production. It was found that the lipid content of Amphiprora sp. was 41.48 ± 0.18%, which was higher than the Pleurosigma sp. (27.3 ± 0.8%) and Amphora sp. (22.49 ± 0.21%). The diatom microalga, Amphiprora sp. was isolated and exposed to a controlled environment. Two different media were prepared, and the main research was on the SiO2-NP medium as the cell wall of diatom was made up of silica. Essential growth parameters were studied such as dry cell weight and chlorophyll a content. The results revealed that Amphiprora sp. cultured in the modified medium showed a higher biomass yield and growth rate in all the analyses. In Soxhlet extraction method, biodiesel yield of Amphiprora sp. in modified medium under 24 μmol m−2 s−1 of light intensity was 81.47 ± 1.59% when using 2% of catalyst amount with 1.5:1 volume ratio of methanol/oil in 3 h reaction time at 65 °C. Results reveled that Amphiprora sp. diatom has a higher yield of oil 52.94 ± 0.42% and can be efficiently optimized with further studies with modified nanomaterial culture medium. The present research revealed the series of experiments on microalgal lipid transesterification and in future investigation different types of nanomaterials should be used in culture medium to identify the lipid production in microalgal cells.